Jogo de papéis e linguagem: diálogos possíveis entre Vigotski e Bakhtin - Couto, Nara Soares [UNESP]; Arena, Dagoberto Buim [UNESP] (My University, 2012)
In this paper we present ongoing research in which we approach the regulatory role of language in role play in children aged six and seven. In research, we seek an understanding of the relationship between language, ownership and complexity of the children's game. The hypothesis guiding the research is that the dialogical relations between children and adults and among children, while playing, contribute to children's learning game. Procedures are being used interpretive ethnographic research that focuses on the human meaning of social relations, waged by the subjects in a particular historical context and its elucidation and exposition by one researcher. This approach allows closer studies of Vygotsky and Bakhtin scholars of language that emphasize the regulatory role of language in human relationships and value the dialogic exchange between researcher and researched; active subjects of the research process. The data were produced by means of observation and interview, in a field diary records, photographs and audio recordings. They are being screened in thematic groups and analyzed using interpretative narration. The participants were two teachers and two classes of the first year of an Elementary school (EMEF) School of Municipal Elementary School Crane, State of Sao Paulo, totaling 45 subjects. Bearing in mind the above assumptions, are presented and analyzed data that allow to anticipate some results.

Neste ensaio apresentamos pesquisa em andamento na qual abordamos o papel regulador da linguagem no jogo de papéis em crianças de seis e sete. Na pesquisa, busca-se um entendimento das relações existentes entre linguagem, apropriação e complexificação do jogo infantil. A hipótese norteadora da investigação é a de que as relações dialógicas entre as crianças e os adultos e entre as crianças, enquanto brincam, contribuem para a aprendizagem do jogo de infantil. Estão sendo utilizados os procedimentos da pesquisa etnográfica interpretativa que tem por foco o significado humano das relações sociais, travadas pelos sujeitos, em um determinado contexto histórico bem como sua elucidação e exposição por um investigador. Essa abordagem permite aproximar os estudos de Vigotski e Bakhtin estudiosos da linguagem que destacam o papel regulador da linguagem nas relações humanas e valorizam as trocas dialógicas entre pesquisador e pesquisado; sujeitos ativos do processo de pesquisa. Os dados foram produzidos por meio de observação e de entrevista, registros em diário de campo, fotografias e gravações em áudio. Eles estão sendo selecionados em grupos temáticos e analisados por meio da narração interpretativa. Participaram da pesquisa duas professoras e duas turmas de primeiro ano do Ensino fundamental de uma (EMEF) Escola Municipal de Ensino Fundamental de Garça, Estado de São Paulo, totalizando 45 sujeitos. Tendo em mente os pressupostos acima, são apresentados e analisados dados que possibilitam antecipar alguns resultados.
Keywords: jogos de papéis; teoria histórico-cultural